Evaluating Genetic Diversity of Agaricus bisporus Accessions through Phylogenetic Analysis Using Single-Nucleotide Polymorphism (SNP) Markers. Issue 1 (2nd January 2021) - Oh, Youn-Lee; Choi, In-Geol; Kong, Won-Sik; Jang, Kab-Yeul; Oh, Min ji; Im, Ji-Hoon
Abstract: Agaricus bisporus, commonly known as the button mushroom, is widely cultivated throughout the world. To breed new strains with more desirable traits and improved adaptability, diverse germplasm, including wild accessions, is a valuable genetic resource. To better understand the genetic diversity available in A. bisporus and identify previously unknown diversity within accessions, a phylogenetic analysis of 360 Agaricus spp. accessions using single-nucleotide polymorphism genotyping was performed. Genetic relationships were compared using principal coordinate analysis (PCoA) among accessions with known origins and accessions with limited collection data. The accessions clustered into four groups based on the PCoA with regard to genetic relationships. A subset of 67 strains, which comprised a core collection where repetitive and uninformative accessions were not included, clustered into 7 groups following analysis. Two of the 170 accessions with limited collection data were identified as wild germplasm. The core collection allowed for the accurate analysis of A. bisporus genetic relationships, and accessions with an unknown pedigree were effectively grouped, allowing for origin identification, by PCoA analysis in this study.